Electrostatic image developing carrier, electrostatic image developer, process cartridge, image forming apparatus and image forming method

The electrostatic image developing carrier with a specific magnetic particle size and flow rate, combined with a resin coating layer containing inorganic particles, addresses the challenge of maintaining density consistency during varying printing conditions, ensuring excellent density change suppression and image quality.

JP7658121B2Active Publication Date: 2025-04-08FUJIFILM BUSINESS INNOVATION CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021043920
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-04-08
Estimated Expiration
2041-03-17

AI Technical Summary

Technical Problem

Existing electrostatic image developing carriers struggle to maintain density consistency during continuous printing with low image amounts followed by high-density printing, especially when the ratio of planar area to surface area, magnetic particle size, and flow rate are outside specific ranges.

Method used

An electrostatic image developing carrier with a magnetic particle and a resin coating layer containing inorganic particles, where the ratio of planar area to surface area is between 1.020 and 1.100, the volume average particle diameter of magnetic particles is 25 μm to 34 μm, and the flow rate is 28 seconds/50 g to 36 seconds/50 g, ensuring excellent density change suppression.

Benefits of technology

The proposed carrier effectively suppresses density changes even during continuous printing with low image amounts followed by high-density printing, maintaining image quality and consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658121000004
    Figure 0007658121000004
  • Figure 0007658121000005
    Figure 0007658121000005
  • Figure 0007658121000001
    Figure 0007658121000001
Patent Text Reader

Abstract

To provide a carrier for electrostatic charge image development excellent in preventing a change in density even when printing with less amount of images are continuously performed and subsequently high-density printing is performed.SOLUTION: A carrier for electrostatic charge image development has a magnetic particle and a resin coating layer that covers the magnetic particle. The resin coating layer includes inorganic particles. The ratio of the surface area B to the plan view area A (B / A) when a carrier surface is three-dimensionally analyzed is 1.020 or more and 1.100 or less. The volume average particle diameter of the magnetic particles is 25 μm or more and 34 μm or less. The fluidity of the magnetic particles is 28 sec / 50 g or more and 36 sec / 50 g or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrostatic image developing carrier, an electrostatic image developer, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]

[0002] Patent Document 1 discloses a carrier core material for electrophotographic developers, characterized in that, when the specific surface area of ​​the carrier core material measured by the BET method is defined as the BET specific surface area and the specific surface area when the carrier core material is assumed to be a true sphere is defined as the equivalent spherical specific surface area, the value of [BET specific surface area] / [equivalent spherical specific surface area] is 8.0 or more and 30.0 or less, the value of surface roughness Ra measured by backscattered electron image analysis with a scanning electron microscope is 0.050 μm or less, and the apparent density is 2.40 g / cc or more.

[0003] Patent Document 2 also describes a magnetic particle having a magnetic core particle and a coating layer that coats the core particle, the shape factor SF-2 being 115 to 150 and the bulk density being 1.8 g / cm. 3 ~2.4g / cm 3 The carrier for developing electrostatic latent images is characterized in that the core particles have a shape factor SF-2 of 120 to 160, an arithmetic mean surface roughness Ra of 0.5 μm to 1.0 μm, and the coating layer contains a resin and a filler in a ratio of 50 parts by mass to 500 parts by mass of the filler per 100 parts by mass of the resin. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2009-086340 A [Patent Document 2] JP 2013-057817 A Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a carrier for developing electrostatic images which has excellent suppression of density change even when high-density printing is performed after successive printing of small image amounts, compared to a case in which the ratio B / A of the planar area A to the surface area B in three-dimensional analysis of the carrier surface is less than 1.020 or exceeds 1.100, the average particle size of the magnetic particles is less than 25 μm or exceeds 34 μm, or the fluidity of the magnetic particles is less than 28 sec / 50 g or exceeds 36 sec / 50 g. [Means for solving the problem]

[0006] Means for solving the above problems include the following aspects. <1> A carrier for developing electrostatic images, comprising magnetic particles and a resin coating layer coating the magnetic particles, the resin coating layer containing inorganic particles, a ratio B / A of a planar area A to a surface area B when the carrier surface is analyzed in three dimensions is 1.020 or more and 1.100 or less, the volume average particle size of the magnetic particles is 25 μm or more and 34 μm or less, and a flowability of the magnetic particles is 28 sec / 50 g or more and 36 sec / 50 g or less. <2> The inorganic particles have an arithmetic mean particle size of 5 nm or more and 90 nm or less. <1> 2. The electrostatic image developing carrier according to claim 1 . <3> The average thickness of the resin coating layer is 0.6 μm or more and 1.4 μm or less. <1> or <2> 2. The electrostatic image developing carrier according to claim 1 . <4> The magnetic particles contain calcium element. <1> ~ <3> 10. The electrostatic image developing carrier according to claim 9, <5> The content of calcium element in the magnetic particles is 0.1% by mass or more and less than 2.0% by mass. <4> 2. The electrostatic image developing carrier according to claim 1 . <6> The BET specific surface area of ​​the magnetic particles is 0.14 m 2 / g or more 0.28m 2 / g or less <1> ~ <5> 10. The electrostatic image developing carrier according to claim 9, <7> The resin coating layer contains an acrylic resin. <1> ~ <6> 10. The electrostatic image developing carrier according to claim 9, <8> The inorganic particles include silica particles. <1> ~ <7> 10. The electrostatic image developing carrier according to claim 9, <9> The silicon element concentration on the surface of the carrier as determined by X-ray photoelectron spectroscopy is more than 2 atomic % and less than 20 atomic %. <8> 2. The electrostatic image developing carrier according to claim 1 . <10> The silicon element concentration is more than 5 atomic % and less than 20 atomic %. <9> 2. The electrostatic image developing carrier according to claim 1 . <11> The content of the inorganic particles is 10% by mass or more and 60% by mass or less with respect to the resin coating layer. <1> ~ <10> 10. The electrostatic image developing carrier according to claim 9, <12> The weight average molecular weight of the resin contained in the resin coating layer is less than 300,000. <1> ~ <11> 13. The electrostatic image developer according to claim 12, <13> The weight average molecular weight of the resin contained in the resin coating layer is less than 250,000. <12> 2. The electrostatic image developing carrier according to claim 1 . <14> a toner for developing an electrostatic image; <1> ~ <14> and the carrier for developing electrostatic images according to any one of the above items. <15> <14> and a developing unit which develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. <16> an image carrier; a charging means for charging a surface of the image carrier; and an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; <14> and developing means for developing an electrostatic image formed on the surface of the image carrier into a toner image using the electrostatic image developer; transferring means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; and fixing means for fixing the toner image transferred to the surface of the recording medium. <17> a charging step of charging a surface of an image carrier; and an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier. <14> a developing step of developing an electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer described in claim 1, a transfer step of transferring the toner image formed on the surface of the image carrier to a surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium. Effect of the Invention

[0007] <1> According to the invention, there is provided a carrier for developing electrostatic images which has excellent suppression of concentration change even when high-density printing is performed after successive printing with a small image volume, compared to a case in which the ratio B / A of the planar area A to the surface area B when the carrier surface is analyzed in three dimensions is less than 1.020 or exceeds 1.100, the volume average particle size of the magnetic particles is less than 25 μm or exceeds 34 μm, or the fluidity of the magnetic particles is less than 28 sec / 50 g or exceeds 36 sec / 50 g. <2> According to the present invention, there is provided a carrier for developing electrostatic images which is more excellent in the suppression of density change as compared with the case where the arithmetic mean particle size of the inorganic particles is less than 5 nm or exceeds 90 nm. <3> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in the suppression of density change, as compared with a case in which the average thickness of the resin coating layer is less than 0.6 μm or exceeds 1.4 μm. <4> According to the present invention, there is provided a carrier for developing electrostatic images, which is more excellent in suppressing density change than when the magnetic particles do not contain calcium element. <5> According to the present invention, there is provided a carrier for developing electrostatic images which is more excellent in the suppression of concentration change compared to when the content of calcium element in the magnetic particles is less than 0.1% by mass or 2.0% by mass or more. <6> According to the present invention, the BET specific surface area of ​​the magnetic particles is 0.14 m 2 / g or less than 0.28m 2 In comparison with the case where the carrier is more than 1 / g, the carrier for developing electrostatic images is more excellent in the suppression of the density change. <7> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in the suppression of density change than when the resin of the resin coating layer is a silicone resin. <8> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in suppressing the concentration change than when the inorganic particles are only alumina particles. <9> According to the present invention, there is provided a carrier for developing electrostatic images, which is more excellent in suppressing concentration change than when the silicon element concentration on the carrier surface determined by X-ray photoelectron spectroscopy is 2 atomic % or less or exceeds 20 atomic %. <10> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in the suppression of concentration change, compared to when the silicon element concentration is 5 atomic % or less or exceeds 20 atomic %. <11> According to the present invention, there is provided a carrier for developing electrostatic images which is more excellent in the suppression of concentration change than when the content of the inorganic particles is less than 10% by mass or more than 60% by mass relative to the resin coating layer. <12> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in the suppression of density change compared to a case where the weight average molecular weight of the resin contained in the resin coating layer is 300,000 or more. <13> According to the present invention, there is provided an electrostatic image developing carrier which is more excellent in the suppression of density change compared to a case where the weight average molecular weight of the resin contained in the resin coating layer is 250,000 or more. <14> ~ <17> According to the invention, an electrostatic image developer, process cartridge, image forming apparatus, or image forming method is provided which has excellent concentration change suppression properties even when high-density printing is performed after successive printing with a small image volume, compared to when the ratio B / A of the planar view area A to the surface area B when the carrier surface is analyzed in three dimensions is less than 1.020 or exceeds 1.100, when the volume average particle size of the magnetic particles is less than 25 μm or exceeds 34 μm, or when the fluidity of the magnetic particles is less than 28 sec / 50 g or exceeds 36 sec / 50 g. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that is detachably mounted to the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0010] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0011] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0013] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0014] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0015] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0016] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic, and "(meth)acrylate" means at least one of acrylate and methacrylate.

[0017] In this disclosure, "toner for developing electrostatic images" is also referred to as "toner", "carrier for developing electrostatic images" is also referred to as "carrier", and "electrostatic image developer" is also referred to as "developer".

[0018] (Electrostatic image developing carrier) The carrier for developing electrostatic images according to this embodiment has magnetic particles and a resin coating layer coating the magnetic particles, the resin coating layer containing inorganic particles, and a ratio B / A of a planar area A to a surface area B when the carrier surface is analyzed in three dimensions is 1.020 or more and 1.100 or less, the volume average particle size of the magnetic particles is 25 μm or more and 34 μm or less, and the flowability of the magnetic particles is 28 sec / 50 g or more and 36 sec / 50 g or less.

[0019] In this embodiment, carbon black is not considered to be an inorganic particle.

[0020] The carrier according to the present embodiment has excellent density change suppression properties (also simply referred to as "density change suppression properties") even when high-density printing is performed after successive printing with a small image amount. The mechanism behind this is presumed to be as follows.

[0021] When printing small amounts of images, such as a document mainly in black with a few color characters, is performed continuously, the toner consumption is small and the toner tends to remain in the developer for a long time, so the charge of the toner tends to increase more than necessary. This is particularly noticeable in color toner. The inventors have found that when high-density printing is performed after successive printings of small amounts of images, the toner is difficult to develop due to the high charge, and the desired image density may not be printed sufficiently. It is presumed that when the toner remains in the developing device for a long time, the charge changes due to the continued charge exchange between the toner and the carrier and the change in the state of the external additives of the toner. When the electrostatic image developing carrier according to the present embodiment is used, the external additive that has been detached from the externally-added toner is not fixed to the carrier surface, and the amount of the external additive attached between the toner surface and the carrier surface is balanced (the external additive moves between the toner and the carrier, and the amount becomes constant, resulting in equilibrium), and it is presumed that the state is unlikely to change over time. Furthermore, when the average particle size and fluidity of the magnetic particles are within the above ranges, the unevenness of the magnetic particle surface is smooth and not sharp, and the unevenness difference between the surface of the resin coating layer and the surface of the magnetic particles exposed on the carrier surface becomes small, so that the above-mentioned equilibrium state is thought to move in a direction in which the external additive is not detached from the toner. This is presumed to be because the force applied to the toner becomes weaker and at the same time, the external additive is less likely to be trapped on the carrier surface. Therefore, it is only by combining the two that it is possible to obtain the effect, and even when high-density printing is performed after continuous printing with a small image amount, an image with little density change can be provided.

[0022] The configuration of the carrier according to this embodiment will be described in detail below.

[0023] <Ratio of planar area A to surface area B when 3D analysis of carrier surface is performed (B / A)> In the carrier of this embodiment, the ratio B / A of the planar area A to the surface area B when the carrier surface is analyzed in three dimensions is 1.020 or more and 1.100 or less, and from the viewpoint of suppressing concentration change, it is preferably 1.040 or more and 1.080 or less, and more preferably 1.040 or more and 1.070 or less.

[0024] In this embodiment, the ratio B / A is an index for evaluating the surface roughness. As an example, the ratio B / A can be determined by the following method. As a device for three-dimensionally analyzing the carrier surface, a scanning electron microscope having four secondary electron detectors (for example, ERA-8900FE, electron beam three-dimensional roughness analyzer manufactured by Elionix Co., Ltd.) is used, and the analysis is performed as follows. The surface of one carrier particle is magnified 5,000 times. The measurement points are spaced 0.06 μm apart, 400 points are measured along the long side and 300 points along the short side, and an area of ​​24 μm x 18 μm is measured to obtain 3D image data. For the three-dimensional image data, the limit wavelength of a spline filter (a frequency-selective filter that uses a spline function) is set to 12 μm to remove wavelengths with a period of 12 μm or more, thereby removing the waviness components of the carrier surface, extracting the roughness components, and obtaining a roughness curve. Furthermore, the cutoff value of a Gaussian high-pass filter (a frequency-selective filter using a Gaussian function) is set to 2.0 μm to remove wavelengths with a period of 2.0 μm or more, thereby removing wavelengths corresponding to the convex parts of the magnetic particles exposed on the carrier surface from the roughness curve after spline filter processing, thereby obtaining a roughness curve from which wavelength components with a period of 2.0 μm or more have been removed. From the 3D roughness curve data after filtering, the central 12 μm × 12 μm area (planar area A = 144 μm 2 ) surface area B (μm 2 ) and calculate the ratio B / A. Calculate the ratio B / A for each of 100 carriers and take the arithmetic average.

[0025] <Magnetic particles> The carrier for developing electrostatic images according to this embodiment has magnetic particles and a resin coating layer that coats the magnetic particles, and the volume average particle size of the magnetic particles is 25 μm or more and 34 μm or less, and the fluidity of the magnetic particles is 28 seconds or more and 36 seconds or less.

[0026] The volume average particle diameter of the magnetic particles is 25 μm or more and 34 μm or less. If the volume average particle diameter is less than 25 μm, the surface area of ​​the carrier becomes too large, the balance of the external additive movement is too far toward the carrier side, and the concentration change suppression performance is poor. If it exceeds 34 μm, the particle diameter is too large, the toner stress becomes too large, and the concentration change suppression performance is poor. From the viewpoint of suppressing concentration changes, the volume average particle size of the magnetic particles is preferably from 26 μm to 33 μm, and more preferably from 28 μm to 32 μm. The volume average particle diameter of the magnetic particles and carrier in this embodiment is a value measured by a laser diffraction particle size distribution measuring device LA-700 (manufactured by Horiba, Ltd.) Specifically, for a particle size range (channel) into which the particle size distribution obtained by the measuring device is divided, the particle diameter at which the cumulative volume distribution is subtracted from the small particle size side and the cumulative 50% is defined as the volume average particle diameter. A suitable method for separating the magnetic particles from the carrier is to dissolve the resin coating layer with an organic solvent and separate the magnetic particles. Another suitable method is the method described below for measuring the BET specific surface area.

[0027] The magnetic particles have a flow rate of 28 sec / 50 g or more and 36 sec / 50 g or less. If the flow rate is less than 28 sec, the surface is smooth, which tends to promote embedding of external additives in the toner, resulting in poor concentration change suppression. If the flow rate is more than 36 sec, the surface has sharp irregularities, which promotes detachment of external additives from the toner and tends to fix the external additives in the gaps between the magnetic particles and the coating layer, resulting in poor concentration change suppression. From the viewpoint of suppressing concentration changes, the fluidity of the magnetic particles is preferably 29 sec / 50 g or more and 35 sec / 50 g or less, more preferably 30 sec / 50 g or more and 34 sec / 50 g or less, and particularly preferably 31 sec / 50 g or more and 33 sec / 50 g or less. The flowability of the magnetic particles in this embodiment is a value measured at 25° C. and 50% RH in accordance with JIS Z2502 (2020).

[0028] As the material of the magnetic particles, a known material used as the core material of the carrier is applied. Specific examples of magnetic particles include particles of magnetic metals such as iron, nickel, and cobalt, particles of magnetic oxides such as ferrite and magnetite, resin-impregnated magnetic particles in which porous magnetic powder is impregnated with resin, and magnetic powder-dispersed resin particles in which magnetic powder is dispersed in resin. In this embodiment, ferrite particles are preferred as the magnetic particles.

[0029] In addition, from the viewpoints of chargeability, chargeability in a high-temperature and high-humidity environment, and suppression of concentration change, the magnetic particles preferably contain calcium element, are more preferably ferrite particles containing calcium element, and are particularly preferably ferrite particles containing iron element, manganese element, magnesium element, and calcium element. When the magnetic particles contain calcium element, the dielectric constant increases, the charge loss at high temperature and high humidity can be suppressed, and the density change suppression property is also excellent.

[0030] From the viewpoints of image quality stability and suppression of density change under high temperature and high humidity conditions, the calcium element content in the magnetic particles is preferably 0.1% by mass or more and less than 2.0% by mass, more preferably 0.2% by mass or more and less than 1.5% by mass, and particularly preferably 0.5% by mass or more and less than 1.0% by mass.

[0031] The calcium element content in the magnetic particles is measured by X-ray fluorescence analysis. The X-ray fluorescence analysis of the ferrite particles is performed by the following method. Qualitative and quantitative analysis is performed using an X-ray fluorescence analyzer (Shimadzu Corporation, XRF1500) under the following conditions: X-ray output: 40V / 70mA, measurement area: diameter 10mm, measurement time: 15 minutes. The elements to be analyzed are selected based on the elements detected in the qualitative analysis. The main elements selected are iron (Fe), manganese (Mn), magnesium (Mg), calcium (Ca), strontium (Sr), oxygen (O), and carbon (C). The mass percentage (%) of each element is calculated by referring to separately prepared calibration curve data.

[0032] The BET specific surface area of ​​the magnetic particles is set to 0.10 m from the viewpoints of long-term image quality stability and suppression of density change.2 / g or more 0.35m 2 / g or less, and 0.14m 2 / g or more 0.28m 2 / g or less is more preferable, and 0.16m 2 / g or more 0.24m 2 In addition, when the coating resin is in the above range, an appropriate amount of the coating resin enters the gaps between the magnetic particles, and deterioration of the resin coating layer due to an anchoring effect can be suppressed, resulting in excellent long-term image quality stability and suppression of density change.

[0033] The BET specific surface area of ​​the magnetic particles is measured using a SA3100 specific surface area measuring device (manufactured by Beckman Coulter) with nitrogen substitution and a three-point method. Specifically, 5 g of magnetic particles are placed in a cell, degassed at 60°C for 120 minutes, and then a mixed gas of nitrogen and helium (30:70) is used. More specifically, the method for separating the magnetic particles from the carrier is as follows: for example, 20 g of the resin-coated carrier is placed in 100 mL of toluene. Ultrasonic waves are applied at 40 kHz for 30 seconds. The magnetic particles and the resin solution are separated using any filter paper according to the particle size. 20 mL of toluene is poured over the magnetic particles remaining on the filter paper to wash them. Next, the magnetic particles remaining on the filter paper are collected. The collected magnetic particles are similarly placed in 100 mL of toluene and ultrasonic waves are applied at 40 kHz for 30 seconds. The magnetic particles are similarly filtered, washed with 20 mL of toluene, and then collected. This is repeated 10 times in total. Finally, the collected magnetic particles are dried, and the BET specific surface area is measured under the above conditions.

[0034] The arithmetic mean height Ra (JIS B0601:2001) of the roughness curve of the magnetic particles is preferably 0.1 μm or more and 1 μm or less, and more preferably 0.2 μm or more and 0.8 μm or less. The arithmetic mean height Ra of the roughness curve of a magnetic particle is determined by observing the magnetic particle at an appropriate magnification (for example, 1000x magnification) using a surface shape measuring device (for example, Keyence Corporation's "Ultra-Deep Color 3D Shape Measuring Microscope VK-9700"), obtaining a roughness curve at a cutoff value of 0.08 mm, and extracting a reference length of 10 μm from the roughness curve in the direction of the average line. The Ra of 100 magnetic particles is calculated as the arithmetic mean.

[0035] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3,000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3,000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.

[0036] The volume resistivity of magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×10 9 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2 The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plate placed on the layer, and then the thickness of the layer (cm) is measured. Both the top and bottom electrodes of the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volumetric electrical resistivity (Ω·cm) of the object being measured is as shown below. R = E × 20 / (II 0 ) / L In the above formula, R is the volume resistivity of the object to be measured (Ω cm), E is the applied voltage (V), I is the current value (A), and I 0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of ​​the electrode plate (cm 2 )

[0037] <Resin coating layer> The electrostatic image developing carrier according to this embodiment has a resin coating layer that coats the magnetic particles, and the resin coating layer contains inorganic particles.

[0038] In the present embodiment, the average thickness of the resin coating layer is preferably from 0.6 μm to 1.4 μm, more preferably from 0.8 μm to 1.2 μm, and particularly preferably from 0.8 μm to 1.1 μm, from the viewpoint of suppressing concentration change.

[0039] Examples of inorganic particles contained in the resin coating layer include metal oxide particles such as silica, titanium oxide, zinc oxide, and tin oxide; metal compound particles such as barium sulfate, aluminum borate, and potassium titanate; and metal particles such as gold, silver, and copper. Among these, silica particles are preferred from the viewpoint of suppressing concentration changes.

[0040] From the viewpoint of suppressing concentration change, the arithmetic average particle size of the inorganic particles in the resin coating layer is preferably 5 nm or more and 90 nm or less, more preferably 5 nm or more and 70 nm or less, even more preferably 5 nm or more and 50 nm or less, and particularly preferably 8 nm or more and 50 nm or less.

[0041] In this embodiment, the average particle size of the inorganic particles contained in the resin coating layer and the average thickness of the resin coating layer are determined by the following method. The carrier is embedded in epoxy resin and cut with a microtome to prepare a carrier cross section. The SEM image of the carrier cross section taken with a scanning electron microscope (SEM) is imported into an image processing analyzer for image analysis. 100 inorganic particles (primary particles) in the resin coating layer are randomly selected, and the circle equivalent diameter (nm) of each is determined and the arithmetic average is taken, which is the average particle size (nm) of the inorganic particles. In addition, 10 locations per carrier particle are randomly selected to measure the thickness (μm) of the resin coating layer, and further measurements are taken for 100 carriers, and all the values ​​are arithmetically averaged, which is the average thickness (μm) of the resin coating layer.

[0042] The surface of the inorganic particles may be subjected to hydrophobic treatment. Examples of the hydrophobic treatment agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobic treatment agent is preferably a silazane compound, and hexamethyldisilazane is preferable. The hydrophobic treatment agent may be used alone or in combination of two or more kinds.

[0043] Examples of methods for hydrophobizing inorganic particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of the inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of the inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to an inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the inorganic particle dispersion and the solution is dried.

[0044] From the viewpoint of suppressing concentration change, the content of inorganic particles contained in the resin coating layer is preferably 10% by mass or more and 60% by mass or less, more preferably 15% by mass or more and 55% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the resin coating layer. From the viewpoint of suppressing concentration change, the content of silica particles contained in the resin coating layer is preferably 10% by mass or more and 60% by mass or less, more preferably 15% by mass or more and 55% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the resin coating layer.

[0045] The silicon element concentration on the carrier surface of the carrier according to this embodiment, determined by X-ray photoelectron spectroscopy, is preferably more than 2 atomic% and less than 20 atomic%, more preferably more than 5 atomic% and less than 20 atomic%, and particularly preferably more than 6 atomic% and less than 19 atomic%, from the viewpoints of long-term image quality stability and suppression of concentration change.

[0046] In this embodiment, the silicon element concentration on the carrier surface is measured by the following method. The carrier is used as a sample and analyzed by X-ray Photoelectron Spectroscopy (XPS) under the following conditions, and the silicon element concentration (atomic %) is calculated from the peak intensity of each element. XPS equipment: ULVAC-PHI, VersaProbe II Etching gun: Argon gun Acceleration voltage: 5kV Emission current: 20mA Sputtering area: 2mm x 2mm Sputtering rate: 3nm / min (SiO 2 Conversion)

[0047] Examples of resins that make up the resin coating layer include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins. In particular, from the viewpoints of electrostatic charge, control of external additive adhesion, and suppression of concentration change, it is preferable that the resin constituting the resin coating layer contains an acrylic resin, it is more preferable that the acrylic resin is contained in an amount of 50 mass% or more, based on the total mass of the resin in the resin coating layer, and it is particularly preferable that the acrylic resin is contained in an amount of 80 mass% or more, based on the total mass of the resin in the resin coating layer.

[0048] From the viewpoint of suppressing concentration change, the resin coating layer preferably contains an acrylic resin having an alicyclic structure. As a polymerization component of the acrylic resin having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (for example, an alkyl (meth)acrylate ester having 1 to 9 carbon atoms in the alkyl group) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more. The acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the acrylic resin having an alicyclic structure.

[0049] The weight average molecular weight of the resin contained in the resin coating layer is preferably less than 300,000, more preferably less than 250,000, even more preferably from 5,000 to less than 250,000, and particularly preferably from 10,000 to 200,000. When in the above range, the smoothness of the resin coating surface of the carrier is increased, so that the amount of external additives attached to the carrier is reduced, and the concentration change suppression property is more excellent.

[0050] The resin coating layer may contain conductive particles for the purpose of controlling electrostatic charge and resistance. Examples of the conductive particles include carbon black and the above-mentioned inorganic particles having electrical conductivity.

[0051] Methods for forming a resin coating layer on the surface of magnetic particles include, for example, a wet method and a dry method. The wet method is a method that uses a solvent to dissolve or disperse the resin that constitutes the resin coating layer. On the other hand, the dry method is a method that does not use the above solvent.

[0052] Examples of wet manufacturing methods include an immersion method in which magnetic particles are immersed in a resin liquid for forming a resin coating layer to coat them, a spray method in which a resin liquid for forming a resin coating layer is sprayed onto the surfaces of magnetic particles, a fluidized bed method in which magnetic particles are fluidized in a fluidized bed and then sprayed with a resin liquid for forming a resin coating layer, and a kneader coater method in which magnetic particles are mixed with a resin liquid for forming a resin coating layer in a kneader coater and the solvent is removed. These manufacturing methods may be repeated or combined. The resin liquid for forming the resin coating layer used in the wet manufacturing method is prepared by dissolving or dispersing the resin, inorganic particles, and other components in a solvent. The solvent is not particularly limited, and examples of the solvent that can be used include aromatic hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, and ethers such as tetrahydrofuran and dioxane.

[0053] An example of the dry manufacturing method is a method in which a mixture of magnetic particles and a resin for forming a resin coating layer is heated in a dry state to form a resin coating layer. Specifically, for example, the magnetic particles and the resin for forming the resin coating layer are mixed in a gas phase and heated to melt, thereby forming a resin coating layer.

[0054] The ratio B / A can be controlled by the manufacturing conditions. For example, in a manufacturing method in which the kneader-coater method is repeated multiple times (e.g., twice) to form a resin coating layer in stages, the mixing time of the particles to be coated and the resin liquid for forming the resin coating layer in the final kneader-coater process is adjusted to control the ratio B / A. The longer the mixing time in the final kneader-coater process, the smaller the ratio B / A tends to be. In another example, in a production method in which a liquid composition containing inorganic particles (which may or may not contain resin) is applied by a spray method to the surface of a resin-coated carrier produced by a kneader coater method, the particle size and content of the inorganic particles contained in the liquid composition, or the amount of the liquid composition applied to the resin-coated carrier, is adjusted to control the ratio B / A.

[0055] The exposed area ratio of the magnetic particles on the carrier surface is preferably 5% to 30%, more preferably 7% to 25%, and even more preferably 10% to 25%. The exposed area ratio of the magnetic particles on the carrier can be controlled by the amount of resin used to form the resin coating layer, and the greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.

[0056] The exposed area ratio of the magnetic particles on the carrier surface is a value determined by the following method. A target carrier and magnetic particles from which the resin coating layer has been removed from the target carrier are prepared. Methods for removing the resin coating layer from the carrier include, for example, a method for removing the resin coating layer by dissolving the resin component with an organic solvent, and a method for removing the resin coating layer by eliminating the resin component by heating at about 800°C. The carrier and magnetic particles are each used as measurement samples, and the Fe concentration (atomic%) on the sample surface is quantified by XPS, and the exposed area ratio (%) of the magnetic particles is calculated by (Fe concentration of the carrier)÷(Fe concentration of the magnetic particles)×100.

[0057] From the viewpoint of suppressing concentration change, the volume average particle size of the carrier is preferably from 25 μm to 36 μm, more preferably from 26 μm to 35 μm, and particularly preferably from 28 μm to 34 μm.

[0058] (Electrostatic image developer) The developer according to the present embodiment is a two-component developer containing the electrostatic image developing carrier according to the present embodiment and a toner. The toner contains toner particles and, if necessary, an external additive.

[0059] The mixture ratio (mass ratio) of the carrier to the toner in the developer is preferably from 100:1 to 100:30, more preferably from 100:3 to 100:20.

[0060] <Toner particles> The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives.

[0061] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0062] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.

[0063] The "crystallinity" of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.

[0064] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0065] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0066] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0067] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, it is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0068] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0069] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0070] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Here, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystalline structure.

[0071] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0072] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0073] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.

[0074] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0075] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0076] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0077] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0078] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, Examples of the dyes include pigments such as ultramarine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0079] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0080] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0081] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0082] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0083] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0084] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0085] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.

[0086] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The volume average particle size (D50v) of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. The particle size distribution based on volume is plotted from the smallest diameter side, and the particle size at which the cumulative 50% is reached is defined as the volume average particle size D50v.

[0087] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.

[0088] -Method of manufacturing toner particles- The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.

[0089] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, the toner particles are produced through a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating resin particles (other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, to fuse and coalesce the aggregated particles, thereby forming toner particles (fusion and coalescence step).

[0090] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.

[0091] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0092] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0093] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0094] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0095] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.

[0096] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.

[0097] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0098] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.

[0099] -Agglomerated particle formation process- Next, the resin particle dispersion liquid, the colorant particle dispersion liquid, and the release agent particle dispersion liquid are mixed together. Then, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0100] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.

[0101] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.

[0102] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably from 0.01 to 5.0 parts by mass, and more preferably from 0.1 to less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.

[0103] -Fusion / unification process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.

[0104] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the aggregated particle dispersion and the resin particle dispersion in which the resin particles are dispersed are further mixed together to aggregate the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles, thereby forming second aggregated particles; and the second aggregated particle dispersion in which the second aggregated particles are dispersed is heated to fuse and coalesce the second aggregated particles, thereby forming toner particles having a core-shell structure.

[0105] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.

[0106] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0107] -External additives- The external additive may be, for example, inorganic particles. Examples of the inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 ) n , Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.

[0108] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0109] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0110] The amount of the external additive is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.

[0111] <Image forming device, image forming method> The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0112] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0113] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder after the transfer of the toner image and before charging; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it after the transfer of the toner image and before charging it. When the image forming apparatus according to the present embodiment is an intermediate transfer type apparatus, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0114] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge that contains the electrostatic charge image developer according to the present embodiment and has the developing means is preferably used.

[0115] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0116] FIG. 1 is a schematic diagram showing the configuration of an image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 1 includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of each color of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.

[0117] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (one example of an intermediate transfer body) 20 is provided, which extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22 and a support roll 24, and runs in a direction from the first unit 10Y toward the fourth unit 10K. A force is applied to the support roll 24 by a spring (not shown) or the like in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wrapped around them. An intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. The developing devices (an example of developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0118] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.

[0119] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer means) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0120] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C. -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0121] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.

[0122] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0123] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0124] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.

[0125] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0126] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0127] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with a resin or the like, art paper for printing, etc. are preferably used.

[0128] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0129] <Process cartridge> The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.

[0130] The process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing means and, as necessary, at least one other means selected from an image carrier, a charging means, an electrostatic image forming means, and a transfer means.

[0131] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0132] FIG. 2 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 2 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 2, 109 denotes an exposure device (an example of an electrostatic image forming means), 112 denotes a transfer device (an example of a transfer means), 115 denotes a fixing device (an example of a fixing means), and 300 denotes a recording paper (an example of a recording medium). EXAMPLES

[0133] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are based on mass.

[0134] In the following description, the volume average particle size refers to a particle size D50v that is 50% cumulative from the small diameter side in a volume-based particle size distribution.

[0135] <Toner Production> -Preparation of colorant particle dispersion 1- Cyan pigment (copper phthalocyanine B15:3 (manufactured by Dainichi Seika Chemicals Co., Ltd.)): 50 parts by mass Anionic surfactant: Neogen SC (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) 5 parts by mass Ion-exchanged water: 200 parts by weight The above was mixed and dispersed for 5 minutes using an Ultra Turrax manufactured by IKA Corporation, and further dispersed for 10 minutes using an ultrasonic bath to obtain a colorant particle dispersion liquid 1 with a solid content of 21%. The volume average particle size was measured using a particle size measuring instrument LA-700 manufactured by Horiba Ltd. and found to be 160 nm.

[0136] -Preparation of release agent particle dispersion 1- Paraffin wax: HNP-9 (manufactured by Nippon Seiro Co., Ltd.): 19 parts by weight Anionic surfactant: Neogen SC (manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 1 part by weight Ion-exchanged water: 80 parts by weight The above was mixed in a heat-resistant container, heated to 90°C, and stirred for 30 minutes. Next, the molten liquid was passed through the bottom of the container into a Gaulin homogenizer, and circulated for three passes under a pressure condition of 5 MPa, after which the pressure was increased to 35 MPa and circulated for another three passes. The emulsion thus obtained was cooled to 40°C or less in the heat-resistant solution, to obtain a release agent particle dispersion 1. The volume average particle size was measured using a particle size measuring instrument LA-700 manufactured by Horiba Ltd. and found to be 240 nm.

[0137] -Resin particle dispersion 1- [Oil layer] Styrene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.): 30 parts by mass n-Butyl acrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.): 10 parts by mass β-Carboxyethyl acrylate (manufactured by Rhodia Nikka Co., Ltd.): 1.3 parts by mass Dodecanethiol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.): 0.4 parts by mass

[0138] [Water layer 1] Ion-exchanged water: 17 parts by weight Anionic surfactant (Dowfax, manufactured by Dow Chemical Company): 0.4 parts by mass

[0139] [Water layer 2] Ion-exchanged water: 40 parts by weight Anionic surfactant (Dowfax, manufactured by Dow Chemical Company): 0.05 parts by mass Ammonium peroxodisulfate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.): 0.4 parts by mass

[0140] The oil layer components and the aqueous layer 1 components were placed in a flask and mixed with stirring to obtain a monomer emulsion dispersion. The aqueous layer 2 components were placed in a reaction vessel, the atmosphere in the vessel was fully replaced with nitrogen, and the reaction system was heated in an oil bath with stirring until the temperature inside the reaction system reached 75°C. The monomer emulsion dispersion was gradually added dropwise to the reaction vessel over a period of 3 hours to carry out emulsion polymerization. After the end of the addition, the polymerization was continued at 75°C and terminated after 3 hours. The volume average particle diameter D50v of the obtained resin particles was measured to be 250 nm using a laser diffraction particle size distribution measuring device LA-700 (manufactured by Horiba, Ltd.), the glass transition point of the resin was measured to be 53°C at a heating rate of 10°C / min using a differential scanning calorimeter (DSC-50, manufactured by Shimadzu Corporation), and the number average molecular weight (polystyrene equivalent) was measured to be 13,000 using a molecular weight measuring device (HLC-8020, manufactured by Tosoh Corporation) using THF as a solvent. As a result, a resin particle dispersion liquid with a volume average particle diameter of 250 nm, solid content of 42%, glass transition point of 52°C, and number average molecular weight Mn of 13,000 was obtained.

[0141] - Preparation of Toner 1 - Resin particle dispersion: 150 parts by mass Colorant particle dispersion: 30 parts by weight Release agent particle dispersion: 40 parts by weight Polyaluminum chloride: 0.4 parts by weight The above components were thoroughly mixed and dispersed in a stainless steel flask using an Ultra Turrax manufactured by IKE Corporation, and then the flask was heated to 48° C. with stirring in a heating oil bath. After maintaining at 48° C. for 80 minutes, 70 parts by mass of the same resin particle dispersion liquid as above was slowly added thereto. After that, the pH of the system was adjusted to 6.0 using a 0.5 mol / L aqueous solution of sodium hydroxide, and the stainless steel flask was sealed, the seal of the stirring shaft was magnetically sealed, and the mixture was heated to 97°C while continuing to stir, and maintained for 3 hours. After the reaction was completed, the mixture was cooled at a temperature drop rate of 1°C / min, filtered, thoroughly washed with ion-exchanged water, and then subjected to solid-liquid separation by Nutsche suction filtration. The mixture was further dispersed in 3,000 parts by mass of ion-exchanged water at 40°C, and stirred and washed at 300 rpm for 15 minutes. This washing operation was repeated five more times, and when the pH of the filtrate reached 6.54 and the electrical conductivity reached 6.5 μS / cm, solid-liquid separation was performed using No. 5A filter paper by Nutsche suction filtration. Next, vacuum drying was continued for 12 hours to obtain toner base particles. The volume average particle diameter D50v of the toner base particles was measured with a Coulter counter and found to be 6.2 μm, and the volume average particle size distribution index GSDv was 1.20. When the shape was observed with a Luzex image analyzer manufactured by Luzex Corporation, it was observed that the particles had a shape factor SF1 of 135 and were potato-shaped. The glass transition point of the toner was 52°C. Furthermore, silica (SiO 2 ) particles and metatitanic acid compound particles with an average primary particle size of 20 nm, which are a reaction product of metatitanic acid and isobutyltrimethoxysilane, were added so that the coverage rate of the toner particle surface was 40%, and mixed in a Henschel mixer to produce Toner 1.

[0142] <Preparation of magnetic particles 1> Fe 2 O 3 1318 parts by mass of Mn(OH) 2 586 parts by mass of Mg(OH) 2 96 parts by mass of CaCO 313 parts by mass of the above were mixed, and a dispersant, water, and zirconia beads with a media diameter of 1 mm were added, and the mixture was crushed and mixed in a sand mill. The zirconia beads were filtered and dried, and then further mixed in a rotary kiln at 20 rpm and 900 ° C to produce a mixed oxide. Next, a dispersant and water were added, and 6.6 parts by mass of polyvinyl alcohol were added, and the mixture was pulverized in a wet ball mill until the volume average particle size was 1.2 μm. Next, the mixture was granulated and dried in a spray dryer so that the dry particle size was 32 μm. Furthermore, the mixture was fired in an electric furnace at a temperature of 1220 ° C for 5 hours in an oxygen-nitrogen mixed atmosphere with an oxygen concentration of 1%. The obtained particles were subjected to a crushing process and a classification process, and then heated in a rotary kiln at 15 rpm and 900 ° C for 2 hours, and similarly subjected to a classification process to obtain magnetic particles 1. The volume average particle size of magnetic particles 1 was 30 μm, and the BET specific surface area was 0.20 m 2 / g.

[0143] <Preparation of magnetic particles 2 to 14> Magnetic particles 2 to 14 were each produced in the same manner as magnetic particle 1, except that the composition and reaction conditions were changed as shown in Table 1.

[0144] [Table 1]

[0145] <Silica particles and calcium carbonate particles added to the carrier resin coating layer> Silica particles: Commercially available hydrophobic silica particles with arithmetic mean particle sizes of 12 nm, 90 nm, 30 nm, or 45 nm were used. Calcium carbonate particles: Commercially available calcium carbonate particles

[0146] <Preparation of Coating Agent for Forming Carrier Resin Coating Layer> [Preparation of Coating Agent] Polycyclohexyl methacrylate (weight average molecular weight: as shown in Table 2): 30 parts Carbon black (Cabot VXC72): 0.5 parts Inorganic particles as listed in Table 2: Amount as listed in Table 2 Toluene: 250 parts Isopropyl alcohol: 50 parts The above materials and glass beads (diameter 1 mm, same amount as toluene) were put into a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (1) with a solid content of 11%.

[0147] (Examples 1 to 22 and Comparative Examples 1 to 6) <Preparation of Resin-Coated Carrier> -Creating Carrier 1- 1,000 parts of the magnetic particles and 570 parts of the coating agent were put into a kneader and mixed at room temperature (25° C.) for 20 minutes, then heated to 70° C. and dried under reduced pressure. Next, the dried product was taken out of the kneader and sieved through a mesh with 75 μm openings to remove coarse powder, thereby obtaining Carrier 1.

[0148] -Creating carriers 2 to 28- Carriers 2 to 26 were obtained in the same manner as carrier 1, except that the magnetic particles, inorganic particles and their amounts added, Mw of polycyclohexyl methacrylate, and the amount of coating agent added were changed as shown in Table 2.

[0149] <Preparation of developer> Any one of Carriers 1 to 28 and Toner 1 were placed in a V blender in a mixing ratio of carrier:toner=100:10 (mass ratio) and stirred for 20 minutes to obtain Developers 1 to 28, respectively.

[0150] <Measurement of the average particle size of silica particles in the resin coating layer> The carrier was embedded in epoxy resin and cut with a microtome to prepare a carrier cross section. SEM images of the carrier cross section taken with a scanning transmission electron microscope (Hitachi, S-4100) were imported into an image processing analyzer (Nireco, Luzex AP) and image analysis was performed. 100 silica particles (primary particles) were randomly selected from the resin coating layer, and the circle equivalent diameter (nm) of each was calculated and the arithmetic average was calculated to obtain the average particle diameter (nm) of the silica particles.

[0151] <Measurement of the average thickness of the resin coating layer> The SEM image was imported into an image processing analyzer (Luzex AP, manufactured by Nireco Corporation) and image analysis was performed. The thickness (μm) of the resin coating layer was measured at 10 randomly selected points per carrier particle, and then measurements were taken for 100 carrier particles, and the arithmetic average of all measurements was calculated to determine the average thickness (μm) of the resin coating layer.

[0152] <Carrier surface analysis> As a device for three-dimensionally analyzing the carrier surface, an electron beam three-dimensional roughness analyzer ERA-8900FE manufactured by Elionix Co., Ltd. The carrier surface analysis using the ERA-8900FE was specifically carried out as follows. The surface of one carrier particle was enlarged 5,000 times, and 300 measurement points were taken along the long side and short side, respectively, to perform 3D measurements, obtaining 3D image data for an area of ​​24μm x 18μm. For the 3D image data, the limit wavelength of the spline filter was set to 12μm to remove wavelengths with a period of 12μm or more, and further, the cutoff value of the Gaussian high-pass filter was set to 2.0μm to remove wavelengths with a period of 2.0μm or more, obtaining 3D roughness curve data. From the 3D roughness curve data, the central 12μm x 12μm area (plan view area A = 144μm) 2 ) surface area B (μm 2 ) was calculated to obtain the ratio B / A. The ratio B / A was calculated for each of 100 carriers and the arithmetic average was calculated.

[0153] <Measurement of silicon element concentration> The carrier was used as a sample and analyzed by X-ray photoelectron spectroscopy (XPS) under the following conditions, and the silicon element concentration (atomic %) was calculated from the peak intensity of each element. XPS equipment: ULVAC-PHI, VersaProbe II Etching gun: Argon gun Acceleration voltage: 5kV Emission current: 20mA Sputtering area: 2mm x 2mm Sputtering rate: 3nm / min (SiO 2 Conversion)

[0154] <Collection of magnetic particles from developer> The carrier was separated from the developer using a 16m mesh. The coating layer of the separated carrier was dissolved using, for example, toluene to extract the magnetic particles. The solvent was changed arbitrarily according to the coating resin. The difference in dissolution was achieved by heating, applying ultrasonic waves, etc. according to the solvent.

[0155] <Volume average particle size of magnetic particles> The volume average particle size of the magnetic particles was measured using a laser diffraction particle size distribution measuring device LA-700 (manufactured by Horiba, Ltd.).

[0156] <Flow rate of magnetic particles> The flowability of the magnetic particles was measured at 25°C and 50% RH in accordance with JIS Z2502 (2020).

[0157] <Measurement of BET specific surface area of ​​magnetic particles> 20 g of the resin-coated carrier was placed in 100 mL of toluene. Ultrasonic waves were applied at 40 kHz for 30 seconds. The magnetic particles and resin solution were separated using any filter paper according to the particle size. 20 mL of toluene was poured over the magnetic particles remaining on the filter paper to wash them. Next, the magnetic particles remaining on the filter paper were collected. The collected magnetic particles were similarly placed in 100 mL of toluene and ultrasonic waves were applied at 40 kHz for 30 seconds. The magnetic particles were similarly filtered, washed with 20 mL of toluene, and then collected. This was repeated 10 times in total. Finally, the collected magnetic particles were dried, and the BET specific surface area was measured under the above conditions.

[0158] <Density change suppression (23°C 55% RH): When high-density printing is performed after continuous printing with low image volume> A modified Fuji Xerox Co., Ltd. Docu Centre C400 machine was adjusted to operate only with cyan, and 1,000 sheets of 100 characters at 12 pt were printed on A4 paper in an environment of 23°C and 55% RH. Then, 100 sheets of 15 cm square solid images were printed. The density of the first sheet of the solid images and the 100th sheet were compared using X-right manufactured by X-right Co., Ltd., and the density difference between them was calculated. The smaller the density difference, the better the density change suppression.

[0159] <Concentration change suppression (28℃ 85% RH)> The evaluation was carried out in the same manner as in the evaluation of the concentration change inhibition property (23°C, 55% RH), except that the evaluation was carried out in an environment of 28°C, 85% RH.

[0160] (Example 23) <Preparation of amorphous resin A> In a three-neck flask, 61 parts by mass of dimethyl terephthalate, 75 parts by mass of dimethyl fumarate, 34 parts by mass of dodecenylsuccinic anhydride, 16 parts by mass of trimellitic acid, 137 parts by mass of bisphenol A ethylene oxide adduct, 191 parts by mass of bisphenol A propylene oxide adduct, and 0.3 parts by mass of dibutyltin oxide were reacted at 180°C for 3 hours under a nitrogen atmosphere while removing water generated by the reaction from the system, and then the temperature was gradually increased to 240°C while reducing the pressure, and the reaction was continued for 2 hours, followed by cooling. In this way, an amorphous resin A having a weight average molecular weight of 17,100 was prepared.

[0161] <Preparation of Crystalline Resin A> In a three-neck flask, 100 parts by mass of dimethyl sebacate, 67.8 parts by mass of hexanediol, and 0.10 parts by mass of dibutyltin oxide were reacted at 185°C for 5 hours under a nitrogen atmosphere while removing water generated during the reaction from the system, and then the temperature was gradually increased to 220°C while reducing the pressure, and the reaction was continued for 6 hours, followed by cooling. Thus, a crystalline resin A having a weight average molecular weight of 33,700 was prepared.

[0162] The melting temperature of this crystalline resin A was determined to be 71°C from the DSC curve obtained by differential scanning calorimetry (DSC) using the "melting peak temperature" as described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."

[0163] <Preparation of Toner 2> 79 parts by mass of amorphous resin A, 7 parts by mass of colorant (CI Pigment Blue 15:1), 5 parts by mass of release agent (paraffin wax, melting temperature 73°C, manufactured by Nippon Seiro Co., Ltd.), and 8 parts by mass of crystalline resin A (melting temperature 71°C) were charged into a Henschel mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) and stirred and mixed at a peripheral speed of 15 m / sec for 5 minutes, and then the resulting stirred mixture was melt-kneaded in an extruder-type continuous kneader. The extruder was set at a supply side temperature of 160° C., a discharge side temperature of 130° C., a supply side temperature of the cooling roll of 40° C., and a discharge side temperature of 25° C. The temperature of the cooling belt was set at 10° C. The resulting molten and kneaded product was cooled, then coarsely pulverized using a hammer mill, then finely pulverized to 6.5 μm using a jet pulverizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd.), and further classified using an elbow jet classifier (manufactured by Nippon Steel Mining Co., Ltd., model: EJ-LABO) to obtain toner particles 2. The toner particles 2 have a volume average particle size of 6.9 μm and an SF1 of 145. Furthermore, 100 parts by mass of toner particles 2 and 1.2 parts by mass of commercially available fumed silica RX50 (manufactured by Nippon Aerosil Co., Ltd.) as an external additive were mixed using a Henschel mixer (manufactured by Mitsui Miike Machinery Works, Ltd.) at a peripheral speed of 30 m / s for 5 minutes to obtain toner 2.

[0164] <Preparation of developer> Carrier 1 and toner 2 were placed in a V blender in a mixing ratio of carrier:toner=100:10 (mass ratio) and stirred for 20 minutes to obtain developer 30 of Example 23.

[0165] Evaluation was carried out in the same manner as in Example 1 using developer 30.

[0166] Example 24 Carrier 29 was produced in the same manner as in Example 1, except that a methyl methacrylate-dimethylaminoethyl methacrylate (mass ratio 99.5:0.5) copolymer (Mw 50,000) was used instead of polycyclohexyl methacrylate. Furthermore, using carrier 29, developer 29 was prepared in the same manner as in Example 1. Evaluation was carried out in the same manner as in Example 1 using developer 29.

[0167] [Table 2]

[0168] [Table 3]

[0169] In addition, the content (mass%) of silica particles and CaCO 3 The particle content (mass %) represents the content relative to the total mass of the resin coating layer.

[0170] From the above results, it can be seen that the present embodiment is superior in suppressing density change compared to the comparative example, even when high-density printing is performed after successive printing with a small image amount. Furthermore, it can be seen that the electrostatic image developing carrier of Example 23 has better suppression of density change than the electrostatic image developing carrier of Example 1, even when printing with a small amount of image is continuously performed under a high temperature and high humidity environment and then high density printing is performed under a high temperature and high humidity environment. [Explanation of symbols]

[0171] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of a cleaning means) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Fixing device (an example of fixing means) 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of a cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium)

Claims

1. Magnetic particles, and a resin coating layer that coats the magnetic particles; the resin coating layer contains inorganic particles, a ratio B / A of a plan view area A to a surface area B when the carrier surface is three-dimensionally analyzed is 1.020 or more and 1.100 or less; The volume average particle size of the magnetic particles is 25 μm or more and 34 μm or less, The magnetic particles have a flowability of 28 sec / 50 g or more and 36 sec / 50 g or less, as measured in accordance with JIS Z2502 (2020) at 25° C. and 50% RH. Carrier for developing electrostatic images.

2. 2. The carrier for developing electrostatic images according to claim 1, wherein the inorganic particles have an arithmetic mean particle size of 5 nm or more and 90 nm or less.

3. 3. The carrier for developing electrostatic images according to claim 1, wherein the average thickness of the resin coating layer is from 0.6 to 1.4 [mu]m.

4. 4. The carrier for developing an electrostatic image according to claim 1, wherein the magnetic particles contain calcium element.

5. 5. The carrier for developing electrostatic images according to claim 4, wherein the content of calcium element in the magnetic particles is 0.1% by mass or more and less than 2.0% by mass.

6. The BET specific surface area of ​​the magnetic particles is 0.14 m 2 / g or more 0.28m 2 6. The carrier for developing electrostatic images according to claim 1, wherein the molecular weight of the carrier is 1 / g or less.

7. 7. The carrier for developing electrostatic images according to claim 1, wherein the resin coating layer contains an acrylic resin.

8. 8. The carrier for developing an electrostatic image according to claim 1, wherein the inorganic particles include silica particles.

9. 9. The carrier for developing an electrostatic image according to claim 8, wherein the silicon element concentration on the surface of the carrier determined by X-ray photoelectron spectroscopy is more than 2 atomic % and less than 20 atomic %.

10. 10. The carrier for developing electrostatic images according to claim 9, wherein the silicon element concentration is more than 5 atomic % and less than 20 atomic %.

11. 11. The carrier for developing electrostatic images according to claim 1, wherein the content of the inorganic particles is from 10% by mass to 60% by mass based on the mass of the resin coating layer.

12. 12. The carrier for developing an electrostatic image according to claim 1, wherein the weight average molecular weight of the resin contained in the resin coating layer is less than 300,000.

13. 13. The carrier for developing electrostatic images according to claim 12, wherein the weight average molecular weight of the resin contained in the resin coating layer is less than 250,000.

14. a toner for developing an electrostatic image; and the carrier for developing an electrostatic image according to any one of claims 1 to 13. Electrostatic image developer.

15. a developing unit that contains the electrostatic image developer according to claim 14 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.

16. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing unit that contains the electrostatic image developer according to claim 14 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:

17. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to claim 14; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

Citation Information

Patent Citations

  • Carrier for electrophotographic developer, developer, image forming method and process cartridge

    JP2008287044A

  • Carrier core material for electrophotographic developer and manufacturing method therefor, carrier for electrophotographic developer, and electrophotographic developer

    JP2009086340A

  • Carrier for developing electrostatic latent image, process cartridge, and image forming device

    JP2013057817A

  • Carrier for electrostatic latent image developer, electrostatic latent image developer including carrier and toner, and process cartridge using the developer

    JP2013088656A

  • Carrier for electrostatic charge image development, developer for electrostatic charge image development, toner cartridge, process cartridge, image forming apparatus, and image forming method

    JP2013195698A